Antibacterial activity of Sappan (Caesalpinia sappan L.) wood methanol extract against Staphylococcus epidermidis - Atunnisa, Waro; Zamzani, Irfan; Nashihah, Siti (Universitas Ahmad Dahlan, 2023)
The entry and proliferation of microorganisms, such as bacteria, cause skin infections. One of the bacteria that causes skin infections is Staphylococcus epidermidis. Sappan (Caesalpinia sappan L.) wood has been known to have various pharmacology activities, one of which is antibacterial, so its activities need to be developed and improved. This study aimed to determine the activity of the methanol extract of Sappan (C. sappan L.) wood as an antibacterial against S. epidermidis. This research was conducted by extracting Sappan wood powder with 96% methanol as solvent using the Ultrasound-Assisted Extraction (UAE) method and testing for antibacterial activity with concentrations of 25%, 50%, 75% and 100% using the disc method. Results showed that the methanol extract of Sappan wood had an antibacterial activity; the highest inhibition zone at a concentration of 75% was 29.25 mm. Sappan wood was expected to be a promising alternative therapy for overcoming acne problems and can increase economic value for the wider community.